Answer

Verified

375k+ views

**Hint:**This problem is from arithmetic progression. We are given three terms in the form of n and they are in A.P. so it is clear that there is a common difference d in two consecutive terms. So we will form two equations in n and d form. One equation from first and second term and the other is from first and third term. On solving them we will get the value of n and d. from that we will find the numbers. So let’s solve it!

**Step by step solution:**

Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.

So let d be the common difference. Then we can write,

\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1

Now on solving the equation above we get,

\[ \Rightarrow 3n + 2 - 2n + 1 = d\]

Taking similar terms on one side we get,

\[ \Rightarrow 3n - 2n + 2 + 1 = d\]

\[ \Rightarrow n + 3 = d\] …….equation1.1

Now the difference in first and third term is 2d. then we can write,

\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2

Now on solving the equation above we get,

\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]

Taking similar terms on one side we get,

\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]

\[ \Rightarrow 4n = 2d\]

So on further simplification,

\[ \Rightarrow n = \dfrac{d}{2}\]

\[d = 2n\]

This is the value of d.

From 1.1 we get \[ \Rightarrow d - n = 3\]

Putting the value of d in the equation above,

\[ \Rightarrow 2n - n = 3\]

\[ \Rightarrow n = 3\]

This is the value of n \[ \Rightarrow n = 3\] .

Now putting the value one by one in the numbers given we get the numbers also.

First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]

Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]

Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]

**Thus the numbers are \[5,11,17\].**

**Note:**

Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.

\[

\Rightarrow n + 3 = d \\

\Rightarrow d - n = 3 \\

\Rightarrow d - \dfrac{d}{2} = 3 \\

\Rightarrow \dfrac{d}{2} = 3 \\

\Rightarrow d = 3 \times 2 = 6 \\

\]

Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]

Then second number \[5 + d = 5 + 6 = 11\]

Then third number \[11 + d = 11 + 6 = 17\]

Recently Updated Pages

Cryolite and fluorspar are mixed with Al2O3 during class 11 chemistry CBSE

Select the smallest atom A F B Cl C Br D I class 11 chemistry CBSE

The best reagent to convert pent 3 en 2 ol and pent class 11 chemistry CBSE

Reverse process of sublimation is aFusion bCondensation class 11 chemistry CBSE

The best and latest technique for isolation purification class 11 chemistry CBSE

Hydrochloric acid is a Strong acid b Weak acid c Strong class 11 chemistry CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

The Buddhist universities of Nalanda and Vikramshila class 7 social science CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Which are the Top 10 Largest Countries of the World?

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Who founded the Nalanda University 1 Mauryan 2 Guptas class 6 social science CBSE